STRUCTURAL AND LITHOLOGICAL CONTROLS OF PEGMATITE MINERALIZATION IN IKARA NORTHWESTERN NIGERIA - A, YUNUSA; A. A., IBRAHIM (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Structural and lithological control of mineralization in the pegmatite of parts of Ikara was studied using field and petrographic studies of the area together with lineaments and structural analysis to determine the controls of mineralization in the area by remote sensing and field measurements. The area is composed of gneisses, schist, quartzite, and granites as major rock types. NE-SW trending joints define the structural trends of the area which is consistent with the regional orientation of the Pan-African deformation. Mineralized pegmatite in the area occurs within the granites, while the unmineralized pegmatites occur in the gneisses and quartzites. The pegmatites in the study area are long and narrow bodies and have no sign of interaction with the enclosing granites except at contact, which ranges from very sharp to gradational. Structural features indicate that pegmatite mineralization in the study area is structurally controlled within dykes, fractures and veins probably associated with the Late Pan-African Orogeny. Gem minerals in the study area occur in pockets within the pegmatite as epigenetic mineralization and beryl constitutes the most important economic mineral. Accessory phases are beryl, amethyst, tantalite and tourmaline